Transglutaminase and cellular motile events: Retardation of proinsulin conversion by glycine methylester. Issue 7 (July 1985) - Alarcon, C.; Valverde, I.; Malaisse, W. J.
Abstract : Glycine methylester, an inhibitor of transglutaminase, decreased glucose-stimulated insulin release and delayed proinsulin conversion in rat pancreatic islets pulselabelle with L-[4-[ 3 H]phenylalanine. Sarcosine methylester, which does not inhibit transglutaminase activity, failed to affect insulin release and proinsulin conversion. The incorporation of L-[4- 3 H]phenylalanine into islet peptides, the ratio of hormonal to total tritiated peptides and the insulin content of the islets failed to be affected by either of these methylesters. It is proposed that transglutaminase participates in the control of motile events involved in both the transfer of proinsulin from its site of synthesis to its site of conversion, and the translocation of insulin from its site of storage to its site of release.